1979
DOI: 10.1210/endo-104-6-1758
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Degradation by Liver Cell Membranes*

Abstract: Liver cell membranes actively degrade insulin, but the mechanism for this process has not been established. Exposure of [ 125 I]iodoinsulin for various times to a liver cell membrane preparation enriched in blood sinusoidal surfaces resulted in the generation of labeled products of varying sizes.Separation of these products on a molecular sieve column demonstrated a progressive decrease in 125 I-labeled material eluting in the insulin peak and an increase in both larger and smaller molecular weight materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Sephadex G-50 chromatography revealed that the insulin associated with the nucleus was equally divided between a peak that was eluted as intact insulin and a peak containing a high molecular weight complex. A similar high molecular weight peak has been reported (27) by many investigators after insulin incubation of cells or plasma membranes and has usually been attributed to insulin-receptor complexes. However, since we failed to detect internalized plasma membrane receptors in the nuclei by two techniques, immunoelectron microscopy and immunoblotting, the high molecular weight peak may represent '25I-labeled insulin complexed with components of the nuclear heterochromatin.…”
Section: Discussionsupporting
confidence: 79%
“…Sephadex G-50 chromatography revealed that the insulin associated with the nucleus was equally divided between a peak that was eluted as intact insulin and a peak containing a high molecular weight complex. A similar high molecular weight peak has been reported (27) by many investigators after insulin incubation of cells or plasma membranes and has usually been attributed to insulin-receptor complexes. However, since we failed to detect internalized plasma membrane receptors in the nuclei by two techniques, immunoelectron microscopy and immunoblotting, the high molecular weight peak may represent '25I-labeled insulin complexed with components of the nuclear heterochromatin.…”
Section: Discussionsupporting
confidence: 79%
“…The nature of the labeled material after exposure to the hepatocytes was also assessed by chromatography on Sephadex G-50 (1.5 X 90 cm) in 1 M acetic acid (9). In some experiments the cells themselves were extracted with 3 M acetic acid containing 6 M urea, 1 ml/liter Triton X-100 and 0.15 M NaCl, and the extract was chromatographed on Sephadex G-50 in 1 M acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…IDE was initially purified from human red blood cells (37) but is also present in a wide range of nucleated cells (www.genecards.org/cgi-bin/carddisp.pl?gene=IDE). Depending on the type of cell, IDE may be located in the cytosol (38,39), peroxisomes (13,40), endosomes (12,41), mitochondria (15), or on the cell membrane (7)(8)(9)(10)(11)42).…”
Section: Discussionmentioning
confidence: 99%
“…IDE is present in human beings, animals, fungi, and plants (2-4; http://merops.sanger.ac.uk/, see distribution within family M16.002: insulysin) and is reported to be expressed in the liver, adipocytes, muscle cells, erythrocytes, and kidney (3)(4)(5) but also in cell types not responsive to insulin (6) (www.genecards.org/cgi-bin/carddisp.pl?gene=IDE). Despite its predominant presence in the cytosol, IDE is also found in small but significant amounts in subcellular compartments such as the plasma membrane, endosomes, peroxisomes, and mitochondria (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%